Redescription of Ophlitaspongia (?) arbuscula Row, 1911 and Ophlitaspongia (?) horrida Row, 1911 from the Red Sea, and their placement in Clathria (Clathria) Schmidt, 1862 - El-Arab, Mohammed Abdel Latif Ezz; Ekins, Merrick (Zootaxa, 2023)
Ophlitaspongia (?) arbuscula Row, 1911 and Ophlitaspongia (?) horrida Row, 1911 from the type locality in the Red Sea, have been re-described based on the type and fresh material from the Red Sea, Egypt. New specimens were used to illustrate the variation within the species. Examination of the type and fresh material indicates both species are unlikely to belong to the genus Ophlitaspongia, due to the possession of echinating (acantho)styles. The presence of a reticulate skeleton indicates Clathria (Clathria) Schmidt, 1862, is the most likely generic assignment for both species.